Digital gap in the students of the community "La Chiquita Canton San Lorenzo, province of Esmeraldas" - Párraga Jacqueline, Vera (SCT Proceedings in Interdisciplinary Insights and Innovations, 2022)
The factors that accentuate the digital gaps in the community "La Chiquita" of San Lorenzo canton in the province of Esmeraldas in the context of the pandemic (2020-2021) are studied. In this way, rural basic education linked to ICTs is approached during the pandemic, with the intention of identifying factors that cause the digital gap, in contrast to the existing inclusion policies. It seeks to point out the proximity or distance between the connectivity binomial in students and teacher training for the use of information and communication technologies, within the teaching-learning process. The health emergency caused by COVID-19 has led to the emergence of a new world order and a new reality, giving rise to some exceptional moments, including the suspension of face-to-face educational activity, motivated by the state of alarm decreed by the Government to contain its spread, and as a consequence, social phenomena, including the Digital Divide, are deepened and made visible. The exceptional situation that has been experienced in Ecuador in recent times, due to the pandemic of covid-19, has generated the closure of all face-to-face educational activity, schools have remained closed since mid-March 2020, as the only option to face-to-face education in educational centers.